Stretchable electrode and preparation method and application thereof
The electrode ink with negative Poisson's ratio structure was prepared through 3D printing technology, and a directional hole perpendicular to the current collector was formed through directional freeze-drying, which solved the problem that existing battery electrodes were difficult to have both flexibility, stretchability and high energy density. Electrodes with high load capacity and high area capacity are achieved.
Patent Information
- Application Number
- CN202410962400.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-18
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-07-18
AI Technical Summary
Existing battery electrodes are difficult to have both flexibility, stretchability, high load capacity, high area capacity and energy density.
Electrode ink with negative Poisson's ratio structure was prepared by 3D printing technology, and a directional channel perpendicular to the current collector was formed by directional freeze-drying to obtain a stretchable electrode.
The flexibility, stretchability and high energy density of the electrode are achieved, the load thickness and load per unit area of the electrode are improved, and the electrochemical performance of the electrode is enhanced.
Smart Images

Figure CN118676316B_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of battery technology, and in particular relates to a stretchable electrode and a preparation method and application thereof. Background Art
[0002] With the rapid development of electric vehicles and consumer electronics, it is crucial to develop batteries with high energy density and fast charging capabilities. Commercial lithium-ion batteries with embedded cathodes, graphite anodes, and liquid electrolytes tend to approach their energy density limits. In addition, there is a growing demand for portable electronic devices with smaller and smaller areas. Therefore, increasing the loading amount of active materials on a limited area by increasing the thickness of the electrode is an effective measure to simultaneously increase the energy density and power density of energy storage devices.
[0003] At present, electrodes are often prepared by printing processes. However, most printed electrodes use traditional structures such as microlattices, grids, and interdigital structures, which are relatively simple in geometric design and not easy to deform. However, they are not suitable for stretchable batteries, thus limiting their application in flexible wearable electronic devices.
[0004] When designing electrode structures with the goal of improving battery performance, especially increasing capacity / energy density without sacrificing too much rate performance or power density, printed electrodes should have high thickness to carry more active materials, as well as strong mechanical strength to provide support during repeated charge and discharge processes. This further limits the application of electrodes in flexible wearable electronic devices. Summary of the invention
[0005] The purpose of this application is to provide a stretchable electrode and its preparation method and application, aiming to solve to a certain extent the problem that existing battery electrodes are difficult to combine flexibility, stretchability, high load capacity, high area capacity and energy density.
[0006] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:
[0007] In a first aspect, the present application provides a method for preparing a stretchable electrode, comprising the following steps:
[0008] preparing an electrode ink comprising an electrode active material, a conductive agent, a rheology modifier and a solvent;
[0009] 3D printing the electrode ink on the surface of the current collector according to a preset negative Poisson's ratio structure to form a printed electrode with a negative Poisson's ratio structure on the surface of the current collector;
[0010] The printed electrode is subjected to directional freeze drying to form directional channels perpendicular to the current collector in the printed electrode to obtain a stretchable electrode.
[0011] In some possible implementations, the negative Poisson's ratio structure includes at least one of a concave hexagonal rotational rigid body structure, a hinged rotational rigid body structure, a chiral rotational rigid body structure, and a wave-shaped rotational rigid body structure.
[0012] In some possible implementations, the 3D printing uses a desktop dispensing machine.
[0013] In some possible implementations, the 3D printing uses a syringe with a needle size of 25 to 30 and a needle inner diameter of 160 μm to 250 μm.
[0014] In some possible implementations, the printing pressure of the 3D printing is 50 psi to 90 psi, and the printing movement speed is 5 mm / s to 8 mm / s.
[0015] In some possible implementations, after the electrode ink is added to the 3D printed syringe, it is centrifuged at a rotation speed of 1000 rpm to 3000 rpm to remove bubbles in the electrode ink.
[0016] In some possible implementations, the directional freeze-drying step includes: constructing a gradually decreasing temperature gradient along the direction from the printed electrode to the current collector to freeze the printed electrode, so that ice crystals grow in a direction perpendicular to the current collector, and then freeze-drying the frozen printed electrode to form a directional channel perpendicular to the current collector in the printed electrode.
[0017] In some possible implementations, the temperature of the directional freeze-drying is not higher than -60°C, and the duration is not less than 48 hours.
[0018] In some possible implementations, the mass ratio of the electrode active material, the conductive agent, and the rheology modifier is (6-8): (1-3): (1-2).
[0019] In some possible implementations, the solid content of the electrode ink is 35% to 45%.
[0020] In some possible implementations, the electrode active material includes a positive electrode active material or a negative electrode active material.
[0021] In some possible implementations, the conductive agent includes at least one of MXene, carbon nanotubes, acetylene black, and conductive carbon black.
[0022] In some possible implementations, the rheology modifier includes at least one of nanocellulose, sodium carboxymethyl cellulose, and styrene-butadiene rubber.
[0023] In some possible implementations, the solvent includes water.
[0024] In some possible implementations, the current collector includes a positive electrode current collector or a negative electrode current collector.
[0025] In some possible implementations, the conductive agent includes Ti3C2T x1 、Nb2CT x2 、Mo2TiC2T x3 、Ta4C3T x4 、Nb4C3T x5 、V2CT x6 At least one MXene in x1 , T x2 , T x3 , T x4 , T x5 , T x6 The surface terminal groups.
[0026] In some possible implementations, the rheology modifier includes at least one nanocellulose selected from the group consisting of cotton cellulose, wood cellulose, bacterial cellulose, and nano-aramid fiber.
[0027] In some possible implementations, the nanocellulose contains hydroxyl groups.
[0028] In some possible implementations, the positive electrode active material includes at least one of metal oxides, polyanion salts, fluorides, sulfides, and selenides.
[0029] In some possible implementations, the negative electrode active material includes at least one of a carbon negative electrode material, a silicon-based negative electrode material, and an alloy negative electrode material.
[0030] In some possible implementations, the positive electrode current collector includes aluminum foil.
[0031] In some possible implementations, the negative electrode current collector includes at least one of copper foil, copper foam, copper mesh, and a three-dimensional nano-copper array.
[0032] In a second aspect, the present application provides a stretchable electrode, comprising a current collector and a 3D printed electrode layer formed on the surface of the current collector, wherein the 3D printed electrode layer is a negative Poisson's ratio structure, and the 3D printed electrode layer has directional channels perpendicular to the current collector.
[0033] In some possible implementations, the directional channels in the 3D printed electrode layer include nanoscale and microscale.
[0034] In some possible implementations, the thickness of the 3D printed electrode layer is 0.5 mm to 2.2 mm.
[0035] In some possible implementations, the loading per unit area of the 3D printed electrode layer is 20 mg cm -2 ~80mg cm -2 .
[0036] In some possible implementations, the stretchable electrode is a positive stretchable electrode or a negative stretchable electrode.
[0037] In some possible implementations, the failure strain of the 3D printed electrode layer is not less than 18%, and the tensile strength is not less than 3 MPa.
[0038] In some possible implementations, the mass specific capacity of the positive stretchable electrode is 140 mAh g -1 ~170mAh g -1 .
[0039] In some possible implementations, the area specific capacity of the positive stretchable electrode is 3 mAh cm -2 ~10mAh cm -2 .
[0040] In some possible implementations, the mass specific capacity of the negative stretchable electrode is 160 mAh g -1 ~200mAh g -1 .
[0041] In some possible implementations, the area specific capacity of the negative stretchable electrode is 3 mAh cm -2 ~15mAh cm -2 .
[0042] In a third aspect, the present application provides a secondary battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte; wherein the positive electrode and / or the negative electrode comprises the above-mentioned stretchable electrode.
[0043] The preparation method of the stretchable electrode provided in the first aspect of the present application, after preparing the electrode ink, the electrode ink is 3D printed onto the surface of the current collector according to the preset negative Poisson's ratio structure to obtain a printed electrode with a negative Poisson's ratio structure. The negative Poisson's ratio structure has good scalability and flexibility. When stretched in only one direction, the electrode with the negative Poisson's ratio structure will expand in all directions. The expansion structure caused by the rotation of the elastic unit reduces the bulk modulus, thereby preventing the generation of volume expansion and effectively alleviating the fracture of the material. The introduction of the negative Poisson's ratio structure gives the electrode excellent flexibility and stretchability, so that the electrode has excellent elastic mechanical properties such as fracture toughness and shear strength. In addition, the use of 3D printing technology can not only realize the efficient printing preparation of complex negative Poisson's ratio structure electrodes, but also increase the unit area load thickness and load of the electrode, thereby increasing the area energy density of the electrode. Then, the printed electrode is subjected to directional freeze drying, and a directional channel perpendicular to the current collector is formed in the printed electrode, which is conducive to electrolyte penetration, shortens the ion transfer path in the vertical direction of the electrode, and improves the ion migration transmission efficiency and conductivity. Therefore, the preparation method of the stretchable electrode in the embodiment of the present application is not only environmentally friendly throughout the preparation process, but also does not require special protective equipment during operation, and is suitable for industrial large-scale production and application. The prepared electrode has the characteristics of flexibility, stretchability, high load capacity, high area capacity and energy density, and has excellent electrochemical performance.
[0044] The second aspect of the present application provides a stretchable electrode, including a current collector and a 3D printed electrode layer formed on the surface of the current collector. The electrode layer is made using 3D printing technology, which not only realizes the efficient printing preparation of complex negative Poisson's ratio structure electrodes, but also can increase the unit area load thickness and load capacity of the electrode, and improve the area energy density of the electrode. The introduction of the negative Poisson's ratio structure gives the electrode layer excellent flexibility and stretchability, so that the electrode has excellent elastic mechanical properties such as fracture toughness and shear strength. In addition, the 3D printed electrode layer has directional channels perpendicular to the current collector, which is conducive to the penetration of the electrolyte, shortens the ion transfer path in the vertical direction of the electrode, and improves the electrochemical properties such as ion migration transmission efficiency and conductivity.
[0045] In the secondary battery provided in the third aspect of the present application, the positive electrode and / or the negative electrode contains the above-mentioned stretchable electrode, which has excellent tensile deformation flexibility, as well as high conductivity, high load capacity, high area capacity and energy density, thereby improving the electrochemical properties of the secondary battery such as rate performance, energy density, and cycle life. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0047] Figure 1 It is a schematic diagram of a process for preparing a stretchable electrode provided in an embodiment of the present application;
[0048] Figure 2 is a schematic diagram of a negative Poisson's ratio structure provided in an embodiment of the present application;
[0049] Figure 3 It is a schematic diagram of the process of preparing a stretchable electrode provided in Example 1 of the present application and a schematic diagram of stretching, bending and twisting of the product;
[0050] Figure 4 1 is a rheological test diagram of the electrode ink provided in Example 1 and Example 2 of the present application, wherein (a) is a relationship diagram between shear rate and viscosity; (b) is a relationship diagram between storage modulus G' and loss modulus G" and shear stress;
[0051] Figure 5 are cross-sectional morphology images of the stretchable electrodes provided in Example 1 and Comparative Example 1 of the present application, wherein (a) is a scanning electron microscope (SEM) image of the stretchable electrode with a vertical channel structure in Example 1, and (b) is a scanning electron microscope (SEM) image of the stretchable electrode with a random channel structure in Comparative Example 1;
[0052] Figure 6 Schematic diagram of the stretching of the stretchable electrode provided in Example 1 of the present application; wherein (a) is a stretching test diagram along the diagonal direction and (b) is a stretching test diagram along the horizontal direction;
[0053] Figure 7 is a strain and stress relationship diagram of the stretchable electrode provided in Example 1 of the present application;
[0054] Figure 8 It is a rate performance diagram of a half-cell assembled with stretchable electrodes provided in Example 1 and Comparative Example 1 of the present application;
[0055] Fig. 9 This is a charge and discharge performance diagram of a full battery assembled with 2, 4, 6 and 8 different layers of LFP electrodes and LTO electrodes 3D printed in an embodiment of the present application. DETAILED DESCRIPTION
[0056] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0057] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0058] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all mean: a, b, c, ab (i.e. a and b), ac, bc, or abc, where a, b, c can be single or multiple.
[0059] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0060] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0061] The weight of the relevant components mentioned in the examples of the present specification can not only refer to the specific content of each component, but also indicate the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components in the examples of the present specification is proportionally enlarged or reduced, it is within the scope disclosed in the examples of the present specification. Specifically, the mass described in the examples of the present specification can be mass units known in the chemical industry such as µg, mg, g, and kg.
[0062] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.
[0063] The term "3D printing" is a type of rapid prototyping technology, also known as additive manufacturing. As a representative advanced technology, 3D printing can build three-dimensional samples with high resolution, high efficiency and versatility through fewer process steps. It is a layer-by-layer deposition process controlled by computer-aided design software to create 3D structures. Diverse 3D structure prototypes can be quickly created through 3D printers. Compared with traditional manufacturing, the production process is more economical, produces less waste, and the preparation process is simpler.
[0064] The term "MXene" refers to a class of two-dimensional inorganic compounds. These materials are composed of transition metal carbides, nitrides or carbonitrides with a thickness of several atomic layers. MXene materials have hydroxyl groups or terminal oxygen on the surface, and they have the metallic conductivity of transition metal carbides. From a morphological point of view, MXene is like a hydrogel that is flattened in the middle of a metal oxide. It has strong conductivity and can completely replace copper and aluminum in wires, so that the resistance to ion movement will be much smaller.
[0065] The first aspect of the present application provides a method for preparing a stretchable electrode, as shown in the attached Figure 1 As shown, the following steps are included:
[0066] S10. Preparing an electrode ink comprising an electrode active material, a conductive agent, a rheology modifier and a solvent;
[0067] S20. 3D printing the electrode ink on the surface of the current collector according to a preset negative Poisson's ratio structure to form a printed electrode with a negative Poisson's ratio structure on the surface of the current collector;
[0068] S30. Directional freeze drying is performed on the printed electrode to form a directional channel perpendicular to the current collector in the printed electrode to obtain a stretchable electrode.
[0069] The first aspect of the present application provides a method for preparing a stretchable electrode. After preparing the electrode ink, the electrode ink is 3D printed onto the surface of the current collector according to a preset negative Poisson's ratio structure to obtain a printed electrode with a negative Poisson's ratio structure. The negative Poisson's ratio structure has good scalability and flexibility. When stretched in only one direction, the electrode with the negative Poisson's ratio structure will expand in all directions. The expansion structure caused by the rotation of the elastic unit reduces the bulk modulus, thereby preventing the generation of volume expansion and effectively alleviating the fracture of the material. The introduction of the negative Poisson's ratio structure gives the electrode excellent flexibility and stretchability, so that the electrode has excellent elastic mechanical properties such as fracture toughness and shear strength. In addition, the use of 3D printing technology can not only achieve efficient printing and preparation of complex negative Poisson's ratio structure electrodes, but also increase the unit area load thickness and load amount of the electrode, thereby increasing the area energy density of the electrode. Moreover, a multi-level pore structure from macropores to micropores and nanopores can be obtained through 3D printing technology, which shows better adaptability and operability compared with other methods of adjusting pore structure such as co-extrusion and sintering, sacrificial agents and magnetic templates, and can also effectively avoid potential damage to the printed electrode structure. Then, the printed electrode is subjected to directional freeze drying to form a directional channel perpendicular to the current collector in the printed electrode, which is conducive to electrolyte penetration, shortens the ion transfer path in the vertical direction of the electrode, improves the ion migration transmission efficiency and conductivity, and effectively improves the power density, rate performance and mechanical properties of the printed electrode. Therefore, the preparation method of the stretchable electrode in the embodiment of the present application, the entire preparation process is not only environmentally friendly, but also does not require special protective equipment during operation, and is suitable for industrial large-scale production and application. The prepared electrode has the characteristics of flexibility, stretchability, high load, high area capacity and energy density, and has excellent electrochemical properties.
[0070] In the above step S10:
[0071] In some possible implementations, the mass ratio of the electrode active material, the conductive agent and the rheology modifier is (6~8): (1~3): (1~2). In this case, the ratio of the electrode active material ensures the capacity of the prepared stretchable electrode, the conductive agent ensures that the prepared stretchable electrode has good conductivity, and the content of the rheology modifier is beneficial to improve the viscosity of the electrode ink and the rheological properties of the regulator, which is beneficial for subsequent 3D printing. Exemplarily, the mass ratio of the electrode active material, the conductive agent and the rheology modifier can be 6:3:1, 6:2:2, 7:1:2, 1:2:1, 8:1:1, 8:1:2, 8:2:1, 8:3:1, etc., typical but non-restrictive arbitrary point values or interval values between any two point values.
[0072] In some possible implementations, the solid content of the electrode ink is 35% to 45%. At this solid content, it is beneficial for both 3D printing and improving the plasticity of the subsequent 3D printed pattern of the electrode ink. Exemplarily, the solid content of the electrode ink can be 35%, 38%, 40%, 42%, 45%, etc., which are typical but non-restrictive arbitrary point values or interval values between any two point values.
[0073] In some possible implementations, the electrode active material includes a positive electrode active material or a negative electrode active material. The stretchable electrode in the embodiment of the present application can be either a positive stretchable electrode or a negative stretchable electrode. When the stretchable electrode is a positive stretchable electrode, the electrode active material is a positive electrode active material; when the stretchable electrode is a negative stretchable electrode, the electrode active material is a negative electrode active material.
[0074] In some possible implementations, the positive electrode active material includes at least one of metal oxides, polyanion salts, fluorides, sulfides, and selenides. In some embodiments, the metal oxides mainly include layered metal oxides and spinel metal oxides, wherein the layered metal oxides mainly include lithium cobalt oxide, lithium nickel oxide, nickel cobalt manganese ternary materials, lithium nickel cobalt aluminum oxide, lithium-rich manganese-based materials, etc.; spinel metal oxides mainly include lithium manganese oxide, lithium nickel manganese oxide, ferrosoferric oxide, lithium vanadate, etc. In some embodiments, the polyanion salts mainly include phosphates, silicates, sulfates, borates, titanates, etc., including lithium iron phosphate (LiFePO4), lithium manganese phosphate (LiMnPO4), lithium iron manganese phosphate (LiMn x Fe 1-x PO4, 0<x<1), lithium vanadium phosphate (Li3V2(PO4)3), lithium vanadium phosphate (LiVOPO4), lithium cobalt phosphate (LiCoPO4), lithium nickel phosphate (LiNiPO4), lithium iron silicate (Li2FeSiO4), lithium ferrous fluoride sulfate (LiFeSO4F), lithium iron borate (LiFeBO3), lithium iron titanate (Li2FeTiO4), etc. In some embodiments, the fluoride includes iron trifluoride, cobalt trifluoride, nickel trifluoride, etc.; the sulfide includes titanium disulfide, iron disulfide, molybdenum disulfide, etc.; the selenide includes niobium triselenide, etc.
[0075] In some possible implementations, the negative electrode active material includes at least one of a carbon negative electrode material, a silicon-based negative electrode material, and an alloy negative electrode material. In some embodiments, the carbon negative electrode material includes soft carbon, hard carbon, natural graphite, artificial graphite, loose graphite, etc. The silicon-based negative electrode material includes crystalline silicon, silicon dioxide, etc. The alloy negative electrode material includes silicon-based alloys, germanium-based alloys, aluminum-based alloys, antimony-based alloys, magnesium-based alloys, and other alloys.
[0076] In some possible implementations, the conductive agent includes at least one of MXene, carbon nanotubes, acetylene black, and conductive carbon black. These conductive agent materials are all beneficial to improving the conductive properties of the stretchable electrode.
[0077] In some possible implementations, the conductive agent includes Ti3C2T x1 、Nb2CT x2 、Mo2TiC2T x3 、Ta4C3T x4 、Nb4C3T x5 、V2CT x6 At least one MXene in x1 、T x2 、T x3 、T x4 、T x5 、T x6 is the surface terminal group. That is, T x1 、T x2 、T x3 、T x4 、T x5 、T x6 represents the surface functional groups on the outermost exposed M layer, exemplarily including -F, -O, -OH and other surface terminal groups. In this case, the conductive agent is MXene, which is a type of 2D transition metal carbide, nitride or carbonitride, and has the characteristics of hydrophilicity, high density, high metal conductivity and redox activity, thus showing good charge storage and transport capabilities. At the same time, the surface functional groups (T x ) such as -O, -OH, and -F endow MXene with hydrophilicity, enabling it to effectively form an aqueous suspension in the electrode ink.
[0078] The MXene-based inks in the embodiments of the present application require extremely high concentrations to obtain printable rheology, allowing them to flow through narrow printing nozzles. At the same time, MXene nanosheets are easily restacked due to van der Waals forces at high concentrations, and ion dynamics are slow. In order to form a stable, uniform, low-concentration MXene water-based 3D printing electrode ink, a rheology modifier is added to the electrode ink, which can help MXene and electrode active materials disperse in water and also provide mechanical strength for the electrode.
[0079] In some possible implementations, the rheology modifier includes at least one of nanocellulose, sodium carboxymethyl cellulose, and styrene-butadiene rubber; these rheology modifier materials can improve the dispersibility of the conductive agent and the electrode active material, and can also improve the mechanical strength of the electrode.
[0080] In some possible implementations, the rheology modifier includes at least one nanocellulose selected from cotton cellulose, wood cellulose, bacterial cellulose, and nano-aramid fiber. In some possible implementations, nanocellulose contains hydroxyl groups. In this case, nanocellulose is used as a rheology modifier because it is rich in hydroxyl groups, can form strong hydrogen bonds with water molecules, has a high negative Zeta potential (-60 mV), and is an effective surfactant that can help conductive agents such as MXene and electrode active materials disperse in water while providing mechanical strength to the electrode. The strong hydrogen bonds between nanocellulose and conductive agents such as MXene further increase the viscosity of the 3D printed electrode ink.
[0081] In some possible implementations, the solvent includes water. In this case, water is used as the solvent so that the prepared electrode ink has the characteristics of being non-toxic, non-flammable, having a low evaporation rate and being environmentally friendly. Avoid using organic solvents such as N-methyl-2-pyrrolidone as the solvent of the electrode ink, which is both expensive and harmful to the human body.
[0082] In some possible implementations, the positive electrode active material or the negative electrode active material, the MXene conductive agent, and the nanocellulose rheology regulator are fully mixed and stirred in a mortar at a mass ratio of (6-8): (1-3): (1-2), and then deionized water is added dropwise until the solid content of the ink is 35%-45%, and then stirred with a planetary vacuum stirrer for about 30 minutes to make it homogenous to obtain an electrode ink.
[0083] In the above step S20:
[0084] In some possible implementations, the current collector includes a positive current collector or a negative current collector. In some possible implementations, the positive current collector includes aluminum foil; in some possible implementations, the negative current collector includes at least one of copper foil, foamed copper, copper mesh, and a three-dimensional nano copper array. When the stretchable electrode is a positive stretchable electrode, ink containing a positive active material is printed on the surface of the positive current collector; when the stretchable electrode is a negative stretchable electrode, ink containing a negative active material is printed on the surface of the negative current collector.
[0085] In some possible implementations, the negative Poisson's ratio structure includes a concave hexagonal rotating rigid body structure (such as the attached Figure 2 (a)), hinged rotating rigid body structure (as shown in the attached Figure 2 (b)), chiral rotation rigid body structure (as shown in the attached Figure 2 (c)), waveform rotating rigid body structure (as shown in the attached Figure 2At least one of (shown in (d)). The negative Poisson's ratio structure of the embodiment of the present application is a special material structure, which is characterized in that when stretched, the material will expand in the lateral direction; and when compressed, the material will shrink in the lateral direction. This phenomenon is opposite to the traditional positive Poisson's ratio material (i.e., lateral contraction when stretched and lateral expansion when compressed). The embodiment of the present application introduces a negative Poisson's ratio structure to give the electrode excellent flexibility and stretchability. Compared with the most commonly used method for preparing stretchable electrodes: depositing active materials on a stretchable elastic substrate, the stretchable electrodes prepared by this method are limited by the deformation capacity of the substrate during stretching or deformation. The study of the embodiment of the present application found that the method of realizing a stretchable electrode is to apply structural engineering technology to reduce the stress applied to the material, which mainly depends on the structural design of the electrode. The special geometric structure can convert the linear strain of the electrode into bending or yield strain, which provides a good opportunity for preparing stretchable electrodes based on rigid materials. Based on this, the embodiment of the present application adopts a negative Poisson's ratio structure. Due to its good scalability and flexibility, when stretched in only one direction, the material with a negative Poisson's ratio structure will expand in all directions. This is because the expansion structure caused by the rotation of the elastic unit reduces the bulk modulus, thereby preventing the occurrence of volume expansion and effectively alleviating the fracture of the material, so that the printed electrode has excellent elastic mechanical properties such as fracture toughness and shear strength.
[0086] In some possible implementations, 3D printing uses a desktop dispensing machine. The embodiment of the present application uses a desktop dispensing machine to perform 3D printing of electrode ink, which is conducive to accurately controlling the effect of 3D printing. The embodiment of the present application uses 3D printing technology, which can not only achieve efficient printing and preparation of complex negative Poisson's ratio structure electrodes, but also make the 3D printed electrodes self-supporting; and printing the electrodes into unique negative Poisson's ratio structures can increase the load thickness and load per unit area of the electrodes, thereby increasing the area energy density of the electrodes. The electrodes are made to have comprehensive properties such as tensile deformation flexibility, high ion transmission efficiency, and high electrochemical performance.
[0087] In some possible implementations, after the electrode ink is added to the syringe for 3D printing, it is centrifuged at a speed of 1000 rpm to 3000 rpm to remove bubbles in the electrode ink. In this case, removing bubbles in the electrode ink is beneficial to improving subsequent printing effects.
[0088] In some possible implementations, 3D printing uses a syringe with a needle model of 25 to 30 and a needle inner diameter of 160 μm to 250 μm. In this case, the syringe needle used in 3D printing has a smaller inner diameter, which is conducive to improving the accuracy of 3D printing and facilitating the design of more precise printing lines and pores. Exemplarily, the needle model of the syringe used in 3D printing can be any typical but non-restrictive point value or an interval value between any two point values, such as 25, 26, 27, 28, 29, 30, etc.; the inner diameter of the needle can be any typical but non-restrictive point value or an interval value between any two point values, such as 160 μm, 170 μm, 180 μm, 190 μm, 200 μm, 210 μm, 220 μm, 240 μm, 250 μm, etc.
[0089] In some possible implementations, the printing pressure of 3D printing is 50 psi~90 psi, and the printing movement speed is 5 mm / s~8 mm / s. The higher the viscosity of the electrode ink, the higher the extrusion pressure required; and the faster the printing movement speed, the finer the printed lines. In the embodiment of the present application, by matching the extrusion pressure and the movement speed, finer printed lines can be obtained, and the printing accuracy and other effects can be improved. Exemplarily, the printing pressure of 3D printing can be 50 psi, 60 psi, 70psi, 80 psi, 90 psi, etc., typical but non-restrictive arbitrary point values or interval values between any two point values; the printing movement speed can be 5 mm / s, 6 mm / s, 7 mm / s, 8 mm / s, etc., typical but non-restrictive arbitrary point values or interval values between any two point values.
[0090] In some embodiments, 3D printing is performed using a desktop dispensing machine (Fisnar F4200N), which is equipped with a syringe filled with ink and a stainless steel needle (30-gauge to 25-gauge needle, inner diameter 160 μm to 250 μm). The electrode ink is gently loaded into a 30 mL plastic syringe and centrifuged at 2000 rpm for 10 minutes to remove bubbles. The negative Poisson's ratio structure designed in CAD is imported into the printer. A pneumatic liquid dispenser (Fisnar DC50) is used to adjust the printing pressure (50 psi to 90 psi), and the movement speed of the nozzle is controlled by a computer program to be 5 mm / s to 8 mm / s, and the electrode ink is 3D printed onto the surface of the current collector to form a printed electrode with a negative Poisson's ratio structure on the surface of the current collector.
[0091] In the above step S30:
[0092] In some possible implementations, the step of directional freeze drying includes: constructing a gradually decreasing temperature gradient along the direction from the printed electrode to the current collector to freeze the printed electrode, so that ice crystals grow in a direction perpendicular to the current collector, and then freeze drying the frozen printed electrode to form a directional channel perpendicular to the current collector in the printed electrode. The embodiment of the present application constructs a gradually decreasing temperature gradient along the direction from the printed electrode to the current collector, so that the temperature of the surface in contact with the current collector in the printed electrode is lower than the surface away from the current collector, and a temperature gradient is formed from low to high. In this case, the ice crystals in the printed electrode will freeze and grow along the direction of the electrode thickness to form ice crystals perpendicular to the current collector. Then freeze drying the frozen printed electrode will form a directional channel perpendicular to the current collector in the printed electrode. It is beneficial to the penetration of electrolyte, shortening the ion transfer path in the vertical direction of the electrode, and improving the ion migration transmission efficiency and conductivity.
[0093] In some possible implementations, the temperature of directional freeze drying is not higher than -60°C and the duration is not less than 48 hours. Under such freeze drying conditions, the printed electrode can be freeze dried efficiently to obtain a printed electrode with directional channels perpendicular to the current collector.
[0094] In some embodiments, a copper table is prepared as a carrier of the electrode, and the copper table is placed in an incubator, with the top of the copper table flush with the incubator. First, liquid nitrogen is poured into the incubator, the liquid level does not exceed the copper column, and it is frozen for 15 minutes to pre-cool the copper table in the incubator. The printed electrode is placed on the surface of the copper table. Since the copper table obtains a low temperature through liquid nitrogen, the printed electrode is placed on it, so that the bottom temperature of the printed electrode is lower than the top temperature, and a temperature gradient is formed from the bottom to the top. When the incubator is well insulated and not affected by the external temperature, ice crystals grow directionally from the bottom of the printed electrode along the upward gradient to introduce directional ice columns perpendicular to the surface of the current collector. The electrode is then placed in a freeze dryer and freeze-dried at -60 ° C for 48 hours to obtain a printed electrode with directional channels.
[0095] In a second aspect, an embodiment of the present application provides a stretchable electrode, comprising a current collector and a 3D printed electrode layer formed on the surface of the current collector, the 3D printed electrode layer being a negative Poisson's ratio structure, and having directional channels perpendicular to the current collector in the 3D printed electrode layer.
[0096] The stretchable electrode provided in the embodiment of the present application includes a current collector and a 3D printed electrode layer formed on the surface of the current collector. The electrode layer is made by 3D printing technology, which not only realizes the efficient printing preparation of complex negative Poisson's ratio structure electrodes, but also can increase the unit area load thickness and load capacity of the electrode, and improve the area energy density of the electrode. The introduction of the negative Poisson's ratio structure gives the electrode layer excellent flexibility and stretchability, so that the electrode has excellent elastic mechanical properties such as fracture toughness and shear strength. In addition, the 3D printed electrode layer has directional channels perpendicular to the current collector, which is conducive to the penetration of electrolyte, shortens the ion transfer path in the vertical direction of the electrode, and improves the electrochemical properties such as ion migration transmission efficiency and conductivity.
[0097] In some possible implementations, the directional channels in the 3D printed electrode layer include nanoscale and microscale. In this case, the 3D printed electrode layer has a multi-level, multi-level channel structure, which significantly shortens the vertical ion transfer path, can accelerate ion transmission, better accelerate ion transmission, and improve ion conductivity. In addition, the three-dimensional multi-level channel structure is conducive to exposing the surface active sites of conductive agents such as MXene in the electrode layer, thereby helping to improve specific capacitance and rate capability.
[0098] In some possible implementations, the thickness of the 3D printed electrode layer is 0.5 mm to 2.2 mm. The electrode layer of the embodiment of the present application is prepared by a 3D printing process, which can increase the thickness of the electrode to carry more electrode active substances and increase the load of the electrode active substances on a limited area, thereby increasing the energy density and power density of the battery. Exemplarily, the thickness of the 3D printed electrode layer can be 0.5 mm, 0.8 mm, 1.0 mm, 1.2 mm, 1.5 mm, 1.8 mm, 2.0 mm, 2.2 mm, etc., typical but non-restrictive arbitrary point values or interval values between any two point values.
[0099] In some possible implementations, the loading per unit area of the 3D printed electrode layer is 20 mg cm -2 ~80 mgcm -2 The 3D printed electrode layer of the embodiment of the present application has a higher loading per unit area, which is beneficial to improve the energy density and power density of the battery. For example, the loading per unit area of the 3D printed electrode layer can be 20 mg cm -2 、30 mg cm -2 , 40mg cm -2 , 50 mg cm -2 、60 mg cm -2 、70 mg cm -2 、80 mg cm -2 Typical but non-limiting arbitrary point values or interval values between any two point values.
[0100] In some possible implementations, the stretchable electrode is a positive stretchable electrode or a negative stretchable electrode.
[0101] In some possible implementations, the failure strain of the 3D printed electrode layer is not less than 18%, and the tensile strength is not less than 3 MPa; in this case, the 3D printed electrode layer of the embodiment of the present application has excellent flexibility and stretchability.
[0102] In some possible implementations, the positive stretchable electrode has a mass specific capacity of 140 mAh g -1 ~170 mAhg -1 For example, the mass specific capacity of the positive stretchable electrode can be 140 mAh g -1 , 150 mAh g -1 , 160 mAh g -1 、170 mAh g -1 Typical but non-limiting arbitrary point values or interval values between any two point values.
[0103] In some possible implementations, the positive stretchable electrode has an area specific capacity of 3 mAh cm -2 ~10 mAhcm -2 For example, the area specific capacity of the positive stretchable electrode can be 3 mAh cm -2 , 5 mAh cm -2 、8 mAh cm -2 , 10 mAh cm -2 Typical but non-limiting arbitrary point values or interval values between any two point values.
[0104] In some possible implementations, the mass specific capacity of the negative stretchable electrode is 160 mAh g -1 ~200 mAhg -1 For example, the mass specific capacity of the negative stretchable electrode can be 160 mAh g -1 、180 mAh g -1 , 190 mAh g -1 , 200 mAh g -1 Typical but non-limiting arbitrary point values or interval values between any two point values.
[0105] In some possible implementations, the negative stretchable electrode has an area specific capacity of 3 mAh cm -2 ~15 mAhcm -2 For example, the area specific capacity of the negative stretchable electrode can be 3 mAh cm-2 , 5 mAh cm -2 , 10 mAh cm -2 、15 mAh cm -2 Typical but non-limiting arbitrary point values or interval values between any two point values.
[0106] The stretchable electrode of the embodiment of the present application can be either a positive stretchable electrode or a negative stretchable electrode. Through the special 3D printing process, combined with the advantages of the negative Poisson's ratio structure and the directional pores perpendicular to the current collector, the stretchable electrode has a high mass specific capacity and area specific capacity, can carry more electrode active substances, and improve the energy density of the electrode. At the same time, it has multi-level channels to accelerate ion transmission, has high conductivity for charge transmission, and has strong mechanical strength, flexibility and stretchability. It not only provides support during repeated charging and discharging processes, but also makes the electrode have better tensile deformation flexibility, which can be fully applied to flexible wearable electronic devices.
[0107] In a third aspect, an embodiment of the present application provides a secondary battery, the secondary battery comprising a positive electrode, a negative electrode, a separator and an electrolyte; wherein the positive electrode and / or the negative electrode comprises the above-mentioned stretchable electrode.
[0108] In the secondary battery of the embodiment of the present application, the positive electrode and / or the negative electrode contains the above-mentioned stretchable electrode, which also has excellent tensile deformation flexibility, as well as high conductivity, high load capacity, high area capacity and energy density and other characteristics, thereby being able to improve the electrochemical properties of the secondary battery such as rate performance, energy density, and cycle life.
[0109] In some possible implementations, the separator can block the passage of electrons and allow the passage of ions. Exemplarily, the separator includes, but is not limited to, at least one material selected from polypropylene fiber, polyacrylonitrile fiber, polyvinyl formal fiber, poly(ethylene terephthalate), polyethylene terephthalate, polyamide fiber, and poly(p-phenylene terephthalamide).
[0110] In some possible implementations, the electrolyte includes at least one soluble metal salt. In some specific embodiments, the metal salt includes LiClO4, LiBF4, LiPF6, LiAsF6, LiCF3SO3, LiTDI, Li[(CF3SO2)2N], Li[(FSO2)2N], Li[(C m F 2m+1 SO2)(C n F 2n+1 SO2)N], wherein m and n are natural numbers. These electrolytic salts can ensure high ionic conductivity of the electrolyte, and do not cause harmful side reactions with electrode materials, electrolytes, diaphragms, etc., and have good chemical stability.
[0111] In some possible implementations, the secondary battery includes at least one of a battery cell, a battery module, and a battery pack.
[0112] In some possible implementations, the battery cell types include lithium-ion batteries, as well as new batteries such as lithium-air batteries and lithium metal batteries.
[0113] In some possible implementations, the battery cells of the present application can be assembled into a battery module, and the number of battery cells contained in the battery module can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module. Further, the battery module can also include a housing with a storage space, and multiple battery cells are stored in the storage space.
[0114] In a possible implementation, the battery cells and / or battery modules may also be assembled into a battery pack, and the number of battery cells or battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0115] In order to enable the above implementation details and operations of the present application to be clearly understood by those skilled in the art, as well as to significantly demonstrate the improved performance of the stretchable electrode and its preparation method and application in the embodiments of the present application, the above technical scheme is illustrated by means of multiple embodiments below.
[0116] Example 1
[0117] A stretchable flexible positive electrode, the preparation diagram of which is shown in the attached figure Figure 3 As shown in (a), the following steps are included:
[0118] 1. 700 mg of the positive electrode active material lithium iron phosphate LFP, 200 mg of the conductive agent MXene and 100 mg of nanocellulose were fully mixed and stirred in a mortar, and then deionized water was added dropwise, and then stirred with a planetary vacuum stirrer for 30 minutes to make it homogenous to obtain the positive electrode ink (LFP / MXene / CNF).
[0119] 2. Use a desktop dispensing robot (Fisnar F4200N) equipped with a syringe filled with ink and a stainless steel needle (30 gauge, inner diameter 160 μm). The ink was gently loaded into a 30 mL plastic syringe and centrifuged at 2000 rpm for 10 minutes to remove bubbles. The negative Poisson's ratio structure designed by CAD was imported into the printer. A pneumatic liquid dispenser (Fisnar DC50) was used to adjust the printing pressure, and the movement speed of the nozzle was controlled by a preset computer program. During printing, the extrusion pressure was set to 90 psi and the nozzle movement speed was 8 mm / s. The positive electrode ink (LFP / MXene / CNF) was 3D printed on aluminum foil to obtain a printed electrode.
[0120] 3. Place the copper table in an incubator with the top of the copper table flush with the incubator. First pour liquid nitrogen into the incubator, making sure the liquid level does not exceed the copper column, so as to pre-cool the copper table in the incubator. Place the printed electrode on the surface of the copper table. Since the copper table is cooled by liquid nitrogen, the printed electrode is placed on it, so that the bottom temperature of the printed electrode is lower than the top temperature, and a temperature gradient is formed from the bottom to the top. When the incubator is well insulated and not affected by the external temperature, ice crystals grow directionally from the bottom of the printed electrode along the upward gradient to introduce directional ice columns perpendicular to the platform. The frozen electrode is then placed in a freeze dryer and freeze-dried at -60 °C for 48 hours to obtain a printed electrode with directional channels, that is, a stretchable flexible positive electrode of LFP / MXene / CNF. As shown in the attached figure Figure 3 As shown in (b), the prepared stretchable electrode can be twisted, bent and stretched arbitrarily and has excellent flexibility and stretchable deformation properties.
[0121] Example 2
[0122] A stretchable flexible negative electrode, the preparation of which comprises the following steps:
[0123] 1. 700 mg of negative electrode active material lithium titanate LTO, 200 mg of conductive agent MXene and 100 mg of nanocellulose were fully mixed and stirred in a mortar, and then deionized water was added dropwise, and then stirred with a planetary vacuum stirrer for 30 minutes to make it homogenous to obtain negative electrode ink (LTO / MXene / CNF).
[0124] 2. Use a desktop dispensing robot (Fisnar F4200N) equipped with a syringe filled with ink and a stainless steel needle (30 gauge, inner diameter 160 μm). The ink was gently loaded into a 30 mL plastic syringe and centrifuged at 2000 rpm for 10 minutes to remove bubbles. The negative Poisson's ratio structure designed by CAD was imported into the printer. A pneumatic liquid dispenser (Fisnar DC50) was used to adjust the printing pressure, and the movement speed of the nozzle was controlled by a preset computer program. During printing, the extrusion pressure was set to 90 psi and the nozzle movement speed was 8 mm / s. The negative electrode ink (LTO / MXene / CNF) was 3D printed on aluminum foil to obtain a printed electrode.
[0125] 3. Place the copper table in an incubator with the top of the copper table flush with the incubator. First pour liquid nitrogen into the incubator, the liquid level does not exceed the copper column, so as to pre-cool the copper table in the incubator. Place the printed electrode on the surface of the copper table. Since the copper table obtains low temperature through liquid nitrogen, the printed electrode is placed on it, so that the bottom temperature of the printed electrode is lower than the top temperature, and a temperature gradient is formed from the bottom to the top. When the incubator is well insulated and not affected by the external temperature, ice crystals grow directionally from the bottom of the printed electrode along the upward gradient to introduce directional ice columns perpendicular to the platform. The frozen electrode is then placed in a freeze dryer and freeze-dried at -60 °C for 48 hours to obtain a printed electrode with directional channels, that is, a stretchable flexible negative electrode of LTO / MXene / CNF.
[0126] Comparative Example 1
[0127] A stretchable flexible positive electrode, the preparation of which comprises the following steps:
[0128] 1. 700 mg of the positive electrode active material lithium iron phosphate LFP, 200 mg of the conductive agent MXene and 100 mg of nanocellulose were fully mixed and stirred in a mortar, and then deionized water was added dropwise, and then stirred with a planetary vacuum stirrer for 30 minutes to make it homogenous to obtain the positive electrode ink (LFP / MXene / CNF).
[0129] 2. Use a desktop dispensing robot (Fisnar F4200N) equipped with a syringe filled with ink and a stainless steel needle (30 gauge, inner diameter 160 μm). The ink was gently loaded into a 30 mL plastic syringe and centrifuged at 2000 rpm for 10 minutes to remove bubbles. The negative Poisson's ratio structure designed by CAD was imported into the printer. A pneumatic liquid dispenser (Fisnar DC50) was used to adjust the printing pressure, and the movement speed of the nozzle was controlled by a preset computer program. During printing, the extrusion pressure was set to 90 psi and the nozzle movement speed was 8 mm / s. The positive electrode ink (LFP / MXene / CNF) was 3D printed on aluminum foil to obtain a printed electrode.
[0130] 3. Place the printed electrode in a refrigerator for freezing, and then place the frozen electrode in a freeze dryer at -60°C for freeze drying for 48 hours to obtain a printed electrode with random pores, i.e., a stretchable flexible positive electrode.
[0131] In order to verify the progress of the embodiments of the present application, the following performance tests were performed on the above embodiments and comparative examples:
[0132] 1. Rheological test of electrode ink: At room temperature, the rheological properties of the ink were measured using a rheometer (MCR72, Thermo Scientific) using the shear viscosity method and the oscillation mode. -2 s -1 ~10 2 s -1 ) Record the apparent viscosity. The test results are shown in the attached Figure 4 As shown in (a), at a shear rate of 0.01 s -1 The apparent viscosities of the positive electrode ink LFP / MXene / CNF of Example 1 and the negative electrode ink LTO / MXene / CNF of Example 2 are 7806 Pa·s and 14006 Pa·s, respectively. High viscosity is more conducive to maintaining the preset shape structure, and the ink exhibits shear thinning behavior, which is conducive to the shaping of the printed structure.
[0133] Dynamic stress sweeps (10 Pa~10 4 Pa), and recorded the storage modulus (G') and loss modulus (G"). The dynamic rheological test was used to further investigate the change of the viscoelasticity of the ink with shear stress. The test results are attached. Figure 4 As shown in (b), when the storage modulus G' is greater than the loss modulus G", the ink exhibits solid behavior; when the stress increases to above the yield stress (i.e., the stress corresponding to the intersection of the two curves G' and G", the network structure breaks, and a solid-liquid transition occurs. The storage modulus values corresponding to the positive electrode ink LFP / MXene / CNF of Example 1 and the negative electrode ink LTO / MXene / CNF platform of Example 2 are 145.37 Pa and 285.77 Pa, respectively. The higher the storage modulus value corresponding to the ink platform and the longer the platform length, the stronger the sample's ability to resist shear force and maintain elastic deformation.
[0134] In summary, the electrode inks prepared in the embodiments of the present application have excellent rheological properties, including significant shear thinning, excellent thixotropy, and high storage modulus G' and yield stress, which ensure their good 3D printing performance.
[0135] 2. The cross-sectional morphology of the stretchable electrodes prepared in Example 1 and Comparative Example 1 was observed: the test results are shown in the attached figure. Figure 5 As shown, Figure 5 (a) is a stretchable electrode with random channels obtained by freezer freezing in comparative example 1. It can be seen that only the pre-designed regular large-sized pores of 3D printing are retained. In contrast, Figure 5(b) is a stretchable electrode with directional channels perpendicular to the current collector obtained by constructing directional freezing in Example 1. It can be seen that vertical micron-scale or even nano-scale holes are generated, thereby significantly increasing the specific surface area of the 3D printed electrode. This favorable three-dimensional structure shortens the ion transmission path and effectively exposes the surface active sites of conductive agents such as MXene, which may improve the specific capacitance and rate capability.
[0136] 3. Testing the advantages of negative Poisson's ratio structure: The stretchable electrode prepared in Example 1 is along the diagonal direction Figure 6 Center (a) and edge directions Figure 6 (b) shows reversible stretchability. The tensile stress-strain curve along the edge direction is shown in Figure 7 As shown, the failure strain of the material is 18.34% and the tensile strength is 3.67 MPa.
[0137] 4. Electrochemical performance test: All battery assemblies were carried out in an argon-filled glove box, and the electrochemical data were collected using a blue battery test system. It was carried out in a liquid electrolyte (1 m LiPF6, ethylene carbonate: dimethyl carbonate in a ratio of 1:1), using a celgard 2325 separator. In the half-cell test, lithium foil was used as the counter electrode and reference electrode. The voltage windows of the LFP / MXene / CNF stretchable flexible positive electrode (referred to as LFP electrode) and the LTO / MXene / CNF stretchable flexible negative electrode (referred to as LTO electrode) are 2 V~4 V and 1 V~2.5 V, respectively. For rate performance testing, the charge and discharge rates ranged from 0.2 C to 5 C.
[0138] As attached Figure 8 As shown in the figure, V refers to the directional pore structure of 3D printing, R refers to the random pore structure of 3D printing, LTO refers to the printed lithium titanate negative electrode, and LFP refers to the printed lithium iron phosphate positive electrode. It can be seen that the positive or negative electrode V-3DP LTO / LFP with a directional pore structure has a better area capacity within a limited area, which is far superior to the positive or negative electrode R-3DP LTO / LFP with a random pore structure.
[0139] Based on this, thicker electrodes with higher areal capacity were printed to evaluate their comprehensive electrochemical performance. According to the above method, 2-layer (0.55 mm thick), 4-layer (1.05 mm thick), 6-layer (1.65 mm thick) and 8-layer (2.20 mm thick) stretchable LFP electrodes and LTO electrodes were prepared and printed respectively. Electrodes of different thicknesses were assembled into half-cells, and the mass specific capacity and area specific capacity of electrodes of different layer thicknesses were tested respectively. Among them, the mass specific capacity and area specific capacity of the half-cell assembled with 2-layer LFP electrodes were 161.9 mAh g -1and 3.44 mAh cm -2 The mass specific capacity and area specific capacity of the half-cell assembled with two layers of LTO electrodes are 184.85 mAh g -1 and 3.65 mAh cm -2 The mass specific capacity and area specific capacity of the half-cell assembled with four layers of LFP electrodes are 161.8 mAh g -1 and 6.46 mAh cm -2 The mass specific capacity and area specific capacity of the half-cell assembled with four layers of LTO electrodes are 174.9 mAh g -1 and 7.21 mAh cm -2 The mass specific capacity and area specific capacity of the half-cell assembled with 6 layers of LFP electrodes are 162.6 mAh g -1 and 9.75 mAh cm -2 The mass specific capacity and area specific capacity of the half-cell assembled with 6-layer LTO electrodes are 168.6 mAh g -1 and 9.84 mAh cm -2 The mass specific capacity and area specific capacity of the half-cell assembled with 8 layers of LFP electrodes are 164.6 mAh g -1 and 13.28 mAh cm -2 The mass specific capacity and area specific capacity of the half-cell assembled with 8-layer LTO electrodes are 164.85 mAh g -1 and 13.02 mAh cm -2 .
[0140] As attached Fig. 9 As shown in the figure, the charge and discharge performance of the full battery assembled with 3D printed 2, 4, 6 and 8 layers of LFP electrodes and LTO electrodes. From the test results, it can be seen that the mass loading is as high as 73.83 mg cm -2 In the case of 8-layer LFP electrode and 8-layer LTO electrode, the mass specific capacity and area specific capacity of the full battery are 140 mAh g -1 and 10.34 mAh cm -2 At the same time, at a current density of 0.2 C, the 8-layer full cell achieved 18.41 mWh cm -2 Ultra-high energy density.
[0141] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A method for preparing a stretchable electrode, characterized in that: The following steps are involved: An electrode ink comprising an electrode active material, a conductive agent, a rheology modifier and a solvent is prepared; wherein the conductive agent comprises MXene, and the rheology modifier comprises at least one hydroxyl-containing nanocellulose selected from cotton cellulose, wood cellulose, bacterial cellulose and nano-aramid fiber; the mass ratio of the electrode active material, the conductive agent and the rheology modifier is (6-8): (1-3): (1-2); The electrode ink is 3D printed on the surface of the current collector according to a preset negative Poisson's ratio structure using a syringe with a needle inner diameter of 160 μm to 250 μm, so as to form a printed electrode with a negative Poisson's ratio structure on the surface of the current collector; the negative Poisson's ratio structure includes at least one of a concave hexagonal rotational rigid body structure, a hinged rotational rigid body structure, a chiral rotational rigid body structure, and a wave-shaped rotational rigid body structure; A gradually decreasing temperature gradient is constructed along the direction from the printed electrode to the current collector so that the temperature of the surface of the printed electrode in contact with the current collector is lower than that of the surface away from the current collector, and the printed electrode is directionally freeze-dried so that ice crystals grow in a direction perpendicular to the current collector to form directional channels perpendicular to the current collector in the printed electrode, thereby obtaining a stretchable electrode; the directional channels include nanoscale and microscale channels, and the unit area loading of the printed electrode layer in the stretchable electrode is 20 mg cm -2 ~80 mg cm -2 ; The failure strain of the printed electrode layer is not less than 18%, and the tensile strength is not less than 3 MPa.
2. The method for preparing a stretchable electrode according to claim 1, wherein: The 3D printing adopts a desktop dispensing machine; And / or, the 3D printing uses a needle model of No. 25 to No. 30; And / or, the printing pressure of the 3D printing is 50 psi to 90 psi, and the printing movement speed is 5 mm / s to 8 mm / s; And / or, after adding the electrode ink to the 3D printed syringe, centrifuge the syringe at a rotation speed of 1000 rpm to 3000 rpm to remove bubbles in the electrode ink.
3. The method for preparing a stretchable electrode according to claim 2, wherein: The temperature of the directional freeze-drying is not higher than -60°C, and the duration is not less than 48 hours.
4. The method for preparing a stretchable electrode according to any one of claims 1 to 3, characterized in that: The solid content of the electrode ink is 35% to 45%; And / or, the electrode active material includes a positive electrode active material or a negative electrode active material; and / or, the solvent comprises water; And / or, the current collector includes a positive electrode current collector or a negative electrode current collector.
5. The method for preparing a stretchable electrode according to claim 4, characterized in that: The conductive agent includes Ti3C2T x1 、Nb2CT x2 、Mo2TiC2T x3 、Ta4C3T x4 、Nb4C3T x5 、V2CT x6 At least one MXene in x1 , T x2 , T x3 , T x4 , T x5 , T x6 is the surface terminal group; And / or, the positive electrode active material includes at least one of metal oxides, polyanion salts, fluorides, sulfides, and selenides; And / or, the negative electrode active material includes at least one of a carbon negative electrode material, a silicon-based negative electrode material, and an alloy negative electrode material; And / or, the positive electrode current collector comprises aluminum foil; And / or, the negative electrode current collector includes at least one of copper foil, copper foam, copper mesh, and three-dimensional nano copper array.
6. A stretchable electrode prepared by the method according to any one of claims 1 to 5, characterized in that: It comprises a current collector and a 3D printed electrode layer formed on the surface of the current collector, wherein the 3D printed electrode layer is a negative Poisson's ratio structure and has directional channels perpendicular to the current collector.
7. The stretchable electrode according to claim 6, wherein: The directional channels in the 3D printed electrode layer include nanometer-scale and micrometer-scale; And / or, the thickness of the 3D printed electrode layer is 0.5 mm to 2.2 mm; And / or, the unit area loading of the 3D printed electrode layer is 20 mg cm -2 ~80 mg cm -2 ; And / or, the stretchable electrode is a positive stretchable electrode or a negative stretchable electrode.
8. The stretchable electrode according to claim 7, wherein: The failure strain of the 3D printed electrode layer is not less than 18%, and the tensile strength is not less than 3 MPa; And / or, the mass specific capacity of the positive stretchable electrode is 140 mAh g -1 ~170 mAh g -1 ; And / or, the area specific capacity of the positive stretchable electrode is 3 mAh cm -2 ~10 mAh cm -2 ; And / or, the mass specific capacity of the negative stretchable electrode is 160 mAh g -1 ~200 mAh g -1 ; And / or, the area specific capacity of the negative stretchable electrode is 3 mAh cm -2 ~15 mAh cm -2 .
9. A secondary battery, characterized in that: The secondary battery comprises a positive electrode, a negative electrode, a separator and an electrolyte; wherein the positive electrode and / or the negative electrode comprises the stretchable electrode according to any one of claims 6 to 8.
Citation Information
Patent Citations
3D-printed high-specific-energy lithium ion battery positive and negative electrode material and preparation method and application thereof
CN114843454A
Combined negative Poisson's ratio flexible electrode imitating butterfly and honeycomb appearance structure
CN115171957A
Low-tortuosity thick electrode based on aqueous binder and preparation and application thereof
CN115692615A
3D printing stretchable aqueous zinc ion battery and preparation method thereof
CN116053611A